Comparative studies of loading lipophilic substances into casein micelles and investigating the influence of whey proteins and heat treatment on loading stability. (8th June 2018) - Moeller, Henrike; Martin, Dierk; Schrader, Katrin; Hoffmann, Wolfgang; Pargmann, Stefanie; Kurz, Janina; Lorenzen, Peter Chr.
Abstract : Application of casein micelles (CM) as nanocarriers for lipophilic substances was studied. Casein micelles were separated from skimmed milk by microfiltration. Casein micelles were partly dissociated at 2 °C, pH 5.5, and loaded with β‐carotene, vitamin D2 or docosahexaenoic acid (DHA). Loading concentrations and times were varied. Loading efficiency was in the order: β‐carotene > vitamin D2 > DHA. Optimal loading times were 60 min for β‐carotene and 15 min for vitamin D2 and DHA. Adding whey protein to loaded CM led to lower vitamin D2 content in the micellar phase. Heat treatment (85 °C/2 min) led to stable loading concentrations over 4 days of storage.